P-617 Cost-effectiveness analysis of In Vitro Fertilization (IVF) antagonist protocols utilizing highly purified human menopausal gonadotropin (HP-hMG) and three different recombinant FSH (rFSH) preparations. (30th June 2022) - Minano Masip, J; Phillips, S; Bissonnette, F; Yuzpe, A; Kadoch, I.J
Abstract: Study question: Is there a mixed ovarian stimulation antagonist protocol for IVF that obtains more good quality blastocysts with less cost? Summary answer: Mixed protocol of HP-hMG and follitropin delta obtains a significantly more good quality blastocysts with significantly lower cost per embryo obtained. What is known already: FSH and LH are used for controlled ovarian stimulation (COS) to increase the number of oocytes produced in IVF. Determination of a stimulation protocol and FSH dosage is generally established by the physician based on the patient's age, body weight and ovarian reserve profile. Mixed protocols (concomitant HP-hMG and rFSH) for ovarian stimulation have been used to obtain better quality oocytes and embryos and thus, higher pregnancy rates compared to the use of rFSH alone. However, to date no data exist comparing cost-effectiveness of mixed protocols using different rFSH preparations. Study design, size, duration: This is a cost-effectiveness analysis of the retrospective cohort study encompassing COS for IVF with 3 different mixed protocols performed between January 2018 and September 2019 in 2 fertility clinics. The 267 subjects evaluated were between 18 and 42 years of age and were divided into 3 groups of 89 subjects each according to the rFSH used: group A follitropin alfa; group B follitropin beta and group D follitropin delta. Participants/materials, setting, methods: HP-hMG was used in all three groups while different rFSH was prescribed. All three groups used an antagonist protocol. IVF or intra-cytoplasmatic sperm injection (ICSI) was used as clinically indicated. Resulting embryos were cultured until day 5 or 6. The dose of gonadotropins used, the number of mature oocytes (MII), the number of utilizable blastocysts and the FSH/blastocyst ratio were evaluated. For cost-effectiveness analysis we used prices accepted by the provincial healthcare system in Quebec. Main results and the role of chance: The mean age of subjects was 34.62 years (± 3.74) and weight 71.65 kg (± 14.61). No significant differences were observed in age or weight among groups. Since follitropin delta is administered in micrograms, the comparison between rFSH preparations was performed using dose equivalence between (10 µg follitropin delta) and (150 IU follitropin alpha and beta). Statistically significant differences were observed among groups in mean total dose of FSH (IU) (A = 4269 IU vs. B = 3947 IU vs. D = 3713 IU, p = 0.01), and number of days of stimulation (A = 11.6 vs. B = 10.6 vs. D = 11.4, p < 0.01). Group D used less gonadotropins despite a longer stimulation. No statistically significant differences were observed in the number of MII oocytes. However, the number of good quality utilizable blastocysts was significantly higher in group D (4.8) than in group A (3.9) or B (3.6). The FSH/blastocyst ratio was significantly lower in group D (370) than in the other groups (A = 541, B = 653). The total price per cycle was similar (A= 4, 028 vs. B= 3, 649 D= 3, 740), however the price per embryo obtained was significantly lower in group D (779) than in the other groups (A= 1, 033, B= 1, 014). Limitations, reasons for caution: The limitation of this cost-effectiveness analysis is the retrospective nature of the study. Wider implications of the findings: Our analysis demonstrates that the price per cycle was similar between the groups, however the price per embryo obtained was significantly lower in group D compared to the other groups. This gives follitropin delta an advantage in terms of cost-effectiveness. Trial registration number: NA